2019
DOI: 10.1109/access.2019.2904679
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Elephant Herding Optimization for Global Optimization

Abstract: The elephant herding optimization (EHO) algorithm is a relatively novel population-based optimization technique, which mimics herding behavior and can be modeled into two operators: clan updating operators and separating operators. Also, in the literature, EHO has received a great deal of attention from researchers since it was proposed applied to many application fields for its advantages of excellent global optimization ability and ease of implementation. However, there is still an insufficiency in the EHO a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 35 publications
0
35
0
Order By: Relevance
“…It has become a significant trend that meta-heuristic algorithms are introduced into SVR parameter adjustment. Mimicking ethological, biological, or physics phenomena is the main means of meta-heuristic algorithms in solving optimization problems [21]. The algorithms applied to SVR include GA [15], [22], FA [4], gray wolf optimization (GWO) [23], PSO [10], ALO [11], DA [12], SSA [13], whale optimization algorithm (WOA) [24], [25], elephant herding algorithm (EHO) [26], simulated annealing (SA) [27], etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has become a significant trend that meta-heuristic algorithms are introduced into SVR parameter adjustment. Mimicking ethological, biological, or physics phenomena is the main means of meta-heuristic algorithms in solving optimization problems [21]. The algorithms applied to SVR include GA [15], [22], FA [4], gray wolf optimization (GWO) [23], PSO [10], ALO [11], DA [12], SSA [13], whale optimization algorithm (WOA) [24], [25], elephant herding algorithm (EHO) [26], simulated annealing (SA) [27], etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With this procedure, it will be shown that the modified algorithm obtains up to 1 m of reduction in the localization error for lower values of noise, when considering the original version, requiring considerably less iterations (regarding the enhanced version, the error will be just slightly lower). For higher values of the noise, it replicates the performance of the original EHO [16] and its enhanced version [18]. The increase in computational effort is compensated by the reduction of the number of iterations, due to substantial increase of the convergence rate.…”
Section: Introductionmentioning
confidence: 78%
“…. , N , β = 2, ξ = 0.7, α = 0.1, population size of 100 elephant divided in 5 clans, and the maximum number of function evaluations of 3000), (3) the Enhanced EHO (EEHO) from [18], and the new iEHO presented in Section III, considering the stopping criteria from eq. 18, where f = 10 −5 .…”
Section: Simulations and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Elhosseini et al [65] presented an improved EHOA to tackle the optimization problems. Ismaeel et al [66] developed an enhanced version of EHOA for global optimization. Jaiprakash & Nanda [67] applied the EHOA for solving the clustering problems.…”
Section: B Elephant Heard Optimization Algorithm (Ehoa)mentioning
confidence: 99%